An Econometric Analysis of Causality between Poverty and Crises in Northern Nigeria - Musa Abdullahi Sakanko (SEISENSE (PRIVATE) LIMITED, 2018)
The study focuses on the analysis of the causality between poverty and crises in northern Nigeria using the Granger causality test and the ARDL bound testing techniques. The study revealed the presence of causality running from poverty to crises and not the other way round as well as co-integration among the pairs. The long-run estimate thus showing poverty exhibiting a positive effect on crises which deviates from the negative relationship obtained in the short-run. The study thus recommends employing poverty reducing mechanism in the region coupled with the overhauling of the agricultural sector as most of the labor force in the region are unskilled which can be easily absorbed in the sector.